Síntese de Zeólita A sem geração de resíduos: avaliação dos parâmetros reacionais para uma rota Eco-Friendly - Santos, Lamara Maciel dos (2020)
There is a huge consumption of synthetic zeolites in the world and zeolite A has been the most used due to its versatility, being used as adsorbent, detergent additive, animal feed and agriculture. However, its route of hydrothermal synthesis does not meet the criteria of sustainability and reduction of residues. Thus, type A zeolite samples were synthesized from an experimental design, aiming to optimize the synthesis process and to evaluate the effect of crystallization time and NaOH/SiO2 and H2O/SiO2 ratios. Additionally, the reuse of separated alkaline mother liquor during filtration was also studied. Significant amount of mother liquor waste is generated in the preparation of zeolitic materials. Recycling is proposed as the best solution for handling such chemical wastes. As a result, it was possible to optimize the synthesis process to obtain crystals of zeolite A, with adequate morphology and crystallinity, in 79 minutes and with a 50% reduction of water and sodium hydroxide content in the synthesis gel. Zeolite A crystals with high crystallinity could also be obtained within 60 min at 100 °C by reusing the mother liquor. The materials were characterized by powder X-ray diffraction and scanning electron microscopy.